Evaluation web-based GNSS software in terms of accuracy - Pirti, Atinc; Yazici, Dilanur (Geomatik Journal, 2022)
Web-based GNSS (Global Navigation Satellite Systems) software allows the user to achieve high accuracy coordinates. Session duration is one of the factors affecting accuracy. In this study, it was aimed to observe the effect of measurement time on the accuracy using AUSPOS (Online GPS Processing Service), CSRS (Canadian Spatial Reference system-Precise Point Positioning) and Trimble RTX from web-based GNSS software. For this purpose, ISTA, IZMI and TUBI stations were selected and 5-day Rinex files belonging to these stations were downloaded. 1, 4, 6, 8, 12, 16, 20, 24 hours of observation files were created using Notepad++ from downloaded files and sent to AUSPOS, CSRS-PPP and Trimble RTX. Trimble RTX was unable to evaluate data from the TUBI station. The conversion to 3 degrees Gauss Kruger coordinates coordinates was done using geographic coordinates obtained from web-based softwares. When the results were examined, it was observed that the AUSPOS service gave higher accuracy than the CSRS-PPP and Trimble RTX services in general.
Keywords: AUSPOS; CSRS-PPP; Trimble RTX; Measurement Time; Accuracy; Geology; Remote Sensing